Análise da estética nasolabial e do impacto na qualidade de vida de pacientes com fissuras labiopalatinas - Ramos, Tânia Braga (2014)
affect the human’s face, creating physical and functional changes due to the aesthetic deficiencies which manifest themselves in the nose and the upper lip area. Hence, the present study aimed to analyze the nasolabial aesthetics of patients with cleft lip and palate by the method of Asher-McDade et al. (1991), correlating it with the quality of life for 8 to 14 year-old children. Through photographs of the face shape characteristics, deviation and nasal profile and the vermilion border of the lip on a 5-point scale were observed. Three examinators, calibrated, evaluated the photographs of front and profile obtained for this purpose, 34 patients with unilateral cleft incisive transforame processed in the Lauro Wanderley University Hospital of the Federal University of Paraíba’s cleft service. Patients and parents also rated the same photographs according to the proposed method. To verify the quality of life, the instruments of the Child Oral Health Quality of Life Questionnaires (COHQoL) were applied to the patients (Child Perceptions Questionnaire-CPQ8-10 and CPQ11-14) and the parents or guardians (Parental-Caregiver Perceptions Questionnaire, P-CPQ). We used descriptive and inferential statistics using the chi-square tests, intraclass correlation coefficient (ICC), reproducibility index (rc), the Kappa coefficient, Pearson correlation (r) and Analysis of Variance (ANOVA) for compare data and associate them with the scores obtained from questionnaires on quality of life, age and gender. The aesthetic results of primary surgery of the patients, seen by professionals, presented indices that indicate very good and looks good in the studied variables: nasal form (70%), nasal deviation (82%), vermilion of the lip (73.5%) and the profile nose (70.5%). When the results given by the professionals were compared to the patients and parents, was observed a significant difference in the classification of aspects analyzed. Regarding the impact of these fissures in quality of life, there was low average, with greater commitment in the area of social and emotional well-being, with regarding to gender and age (p <0.05). No statistically significant differences between the age of completion of the lip repair and palatoplasty surgeries with the scores obtained in the analysis of nasolabial aesthetics were observed. Thus, it can be concluded that the evaluation of nasolabial recommended by professional aesthetic was distinct from that found for patients / parents who are more stringent in recent results obtained with respect to the primary surgeries, and may be an important aspect of life and social emotional patient.